Jinnah : Creator of Pakistan - Bolitho, Hector (Karachi Oxford University Press, 2006)
Political biography of Mohammed Ali Jinnah, 1876-1948, statesman and founder of Pakistan.
Include Bibliography and Index
Keywords: Jinnah, Mahomed Ali, 1876-1948 -- Statesmen -- Pakistan -- India